Revising the classification of somatoform disorders: key questions and preliminary recommendations. - Kroenke, K; Sharpe, M; Sykes, R (2007)
As the DSM-V process unfolds, Somatoform Disorders are a diagnostic category for which major revisions seem warranted. The Conceptual Issues in Somatoform and Similar Disorders (CISSD) project recently convened three workshops, involving 24 experts. The CISSD identified key questions related to stakeholders; terminology; appropriate axis (I versus III); medically unexplained criteria; status of functional somatic syndromes; and symptom counts, grouping, lifetime recall, and checklists. Preliminary recommendations include substantial revision of the category of Somatization Disorder, elimination of Undifferentiated Somatoform Disorder and Pain Disorder, terminology changes, and potential shifting of certain disorders to different DSM categories or axes.